At Westonci.ca, we connect you with the best answers from a community of experienced and knowledgeable individuals. Experience the ease of finding quick and accurate answers to your questions from professionals on our platform. Connect with a community of professionals ready to help you find accurate solutions to your questions quickly and efficiently.
Sagot :
To determine the overall equation for the reaction that produces \(P_4O_{10}\) from \(P_4O_6\) and \(O_2\), we need to follow these steps:
1. Identify the Given Equations:
[tex]\[ \begin{array}{l} P_4(s) + 3 O_2(g) \rightarrow P_4O_6(s) \\ P_4(s) + 5 O_2(g) \rightarrow P_4O_{10}(s) \end{array} \][/tex]
2. Determine the Chemical Equation to Combine:
We need \(P_4O_6\) and \(O_2\) as reactants, resulting in \(P_4O_{10}\) as a product. To do so, we should subtract the first equation from the second one.
3. Balance the Reactants and Products:
On subtracting the first equation from the second:
Cancel out the common reactant \(P_4(s)\)
Adjust the \(O_2(g)\) molecules and the corresponding products.
First reaction:
[tex]\[ P_4(s) + 3 O_2(g) \rightarrow P_4O_6(s) \][/tex]
Second reaction:
[tex]\[ P_4(s) + 5 O_2(g) \rightarrow P_4O_{10}(s) \][/tex]
Subtract the coefficients of the first reactants from the reactants of the second:
[tex]\[ P_4(s) + 5 O_2(g) \rightarrow P_4O_{10}(s) \][/tex]
Minus:
[tex]\[ P_4(s) + 3 O_2(g) \rightarrow P_4O_6(s) \][/tex]
This gives:
[tex]\[ (5 O_2(g) - 3 O_2(g)) \rightarrow P_4O_{10}(s) - P_4O_6(s) \][/tex]
Simplifies to:
[tex]\[ 2 O_2(g) + P_4O_6(s) \rightarrow P_4O_{10}(s) \][/tex]
4. Conclusion:
The overall chemical equation that produces \(P_4O_{10}\) from \(P_4O_6\) and \(O_2\) becomes:
[tex]\[ P_4O_6(s) + 2 O_2(g) \rightarrow P_4O_{10}(s) \][/tex]
Therefore, the correct equation is:
[tex]\[ P_4O_6(s) + 2 O_2(g) \rightarrow P_4O_{10}(s) \][/tex]
1. Identify the Given Equations:
[tex]\[ \begin{array}{l} P_4(s) + 3 O_2(g) \rightarrow P_4O_6(s) \\ P_4(s) + 5 O_2(g) \rightarrow P_4O_{10}(s) \end{array} \][/tex]
2. Determine the Chemical Equation to Combine:
We need \(P_4O_6\) and \(O_2\) as reactants, resulting in \(P_4O_{10}\) as a product. To do so, we should subtract the first equation from the second one.
3. Balance the Reactants and Products:
On subtracting the first equation from the second:
Cancel out the common reactant \(P_4(s)\)
Adjust the \(O_2(g)\) molecules and the corresponding products.
First reaction:
[tex]\[ P_4(s) + 3 O_2(g) \rightarrow P_4O_6(s) \][/tex]
Second reaction:
[tex]\[ P_4(s) + 5 O_2(g) \rightarrow P_4O_{10}(s) \][/tex]
Subtract the coefficients of the first reactants from the reactants of the second:
[tex]\[ P_4(s) + 5 O_2(g) \rightarrow P_4O_{10}(s) \][/tex]
Minus:
[tex]\[ P_4(s) + 3 O_2(g) \rightarrow P_4O_6(s) \][/tex]
This gives:
[tex]\[ (5 O_2(g) - 3 O_2(g)) \rightarrow P_4O_{10}(s) - P_4O_6(s) \][/tex]
Simplifies to:
[tex]\[ 2 O_2(g) + P_4O_6(s) \rightarrow P_4O_{10}(s) \][/tex]
4. Conclusion:
The overall chemical equation that produces \(P_4O_{10}\) from \(P_4O_6\) and \(O_2\) becomes:
[tex]\[ P_4O_6(s) + 2 O_2(g) \rightarrow P_4O_{10}(s) \][/tex]
Therefore, the correct equation is:
[tex]\[ P_4O_6(s) + 2 O_2(g) \rightarrow P_4O_{10}(s) \][/tex]
Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We hope this was helpful. Please come back whenever you need more information or answers to your queries. Find reliable answers at Westonci.ca. Visit us again for the latest updates and expert advice.